2011
DOI: 10.1200/jco.2010.34.4614
|View full text |Cite
|
Sign up to set email alerts
|

Antiemetics: American Society of Clinical Oncology Clinical Practice Guideline Update

Abstract: Combined anthracycline and cyclophosphamide regimens were reclassified as highly emetic. Patients who receive this combination or any highly emetic agents should receive a 5-HT(3) receptor antagonist, dexamethasone, and a neurokinin 1 (NK(1)) receptor antagonist. A large trial validated the equivalency of fosaprepitant, a single-day intravenous formulation, with aprepitant; either therapy is appropriate. Preferential use of palonosetron is recommended for moderate emetic risk regimens, combined with dexamethas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
430
1
43

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 801 publications
(479 citation statements)
references
References 28 publications
5
430
1
43
Order By: Relevance
“…Guidelines currently recommend that a 5‐HT 3 RA and dexamethasone be used in all patients receiving MEC and that patients with additional CINV risk factors also receive an NK‐1 RA 4, 5…”
Section: Introductionmentioning
confidence: 99%
“…Guidelines currently recommend that a 5‐HT 3 RA and dexamethasone be used in all patients receiving MEC and that patients with additional CINV risk factors also receive an NK‐1 RA 4, 5…”
Section: Introductionmentioning
confidence: 99%
“…"bolesti kretanja"); -ima anamnezu povraćanja u trudnoći; -iskusio mučninu i povraćanje u prethodnim ciklusima hemioterapije, pogotovu ako su mučnina i / ili povraćanje bili težeg stepena -anksiozan -koristi neke druge lekove (na primer, nesteroidne antiinflamatorne lekove, opioide ili antibiotike) -Hronična teška zloupotreba alkoholnih pića smanjuje rizik za nastanak mučnine i povraćanja uzrokovanih hemioterapijom. (7,8,9,10) Najvažniji faktor za ispoljavanje mučnine i povraćanja jeste emetogentost citotoksičnih lekova i njome se treba rukovoditi u terapijskom pristupu u prevenciji mučnine i povraćanja. Kada se radi o hemioterapijskim režimima koji obuhvataju dva ili više citotoksična leka, emetogenost režima određuje emetogenost najemetogenijeg leka u kombinaciji.…”
Section: Faktori Rizika Pacijentaunclassified
“…Kada se radi o hemioterapijskim režimima koji obuhvataju dva ili više citotoksična leka, emetogenost režima određuje emetogenost najemetogenijeg leka u kombinaciji. (6,7,9,10) Mučnina i povraćanje koji su izazvani hemioterapijom negativno utiču na kvalitet života pacijenata i na potrošnju sredstava zdravstvene zaštite. Kontrola emetegenosti hemioterapije i dalje ostaje izazov , a nedostatak efikasne komunikacije između pacijenta i lekara i medicinskih sestara je istaknut u literaturi kao glavna prepreka za optimalnu kontrolu.…”
Section: Faktori Rizika Pacijentaunclassified
“…The guidelines recommend using the combination of dexamethasone, 5-hydroxytryptamine 3 (5-HT 3 ) receptor antagonist and neurokinin-1 (NK 1 ) receptor antagonist for prevention of CINV associated with HEC (6)(7)(8)(9). It has been shown that adherence to the antiemetic guideline leads to an improvement of the control of CINV (10)(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Cisplatin is classified as chemotherapy with high emetic risk (HEC) in several guidelines for prevention of chemotherapy-induced nausea and vomiting (CINV) (6)(7)(8)(9).…”
mentioning
confidence: 99%